The Limits of Electoral Control: Evidence from Last‐Term Politicians. Issue 4 (2nd May 2016) - Geys, Benny; Mause, Karsten
Abstract : In modern democracies, politicians' accountability is often linked to the disciplining mechanism of electoral control. For politicians in their final term, this mechanism is impaired. Using a novel data set covering 910 members of the UK House of Commons active within the period 1997–2010, we investigate how reduced electoral control affects last‐term MPs' trade‐off between work effort inside parliament, leisure, and outside interests. Our main contributions lie in providing the first explicit consideration of (1) MPs' final‐term intra‐/extraparliamentary work balance and (2) MPs' reasons for leaving parliament (i.e., retirement, career change, electoral defeat). These extensions provide important fresh insights concerning the boundaries of elections' disciplining power.